Plantas medicinais e saúde bucal: uma abordagem etnobotânica em comunidades quilombolas do agreste paraibano - Bertanha, Wânia de Fátima Faraoni (2011)
Ethnobotany can rescue knowledge and traditional practices about medicinal plants. Quilombo (Brazilian hinterland settlements) communities are population groups that hold such knowledge. This study its aims are to survey an ethnpbothany approach of the medicinal plants used oral diseases by three quilombo communities in the agreste region of the State of Paraíba: Caiana dos Crioulos, Sítio Matias and Grilo.This study is ethnobotanical, descriptive, participatory observational study, with a quantitative approach. The population consists of 240 families and the sampling is of the non-probabilistic intentional type, known as "snow ball". The research was carried out using a semi-structured interview and the results were analyzed using descriptive statistics. In total, 26 people were interviewed, 5 males and 21 females, aged 20 to 80 years. The botanical specimens were collected with the usual techniques for collecting material in the field. The plants that were studied were deposited in the Herbarium of the State University of Paraíba. There were 39 plants belonging to 31 families, cited as treatments for toothache, inflammation, abscesses, tooth brushing, tooth eruption e thrush. The most frequently mentioned were Anacardium occidentale L.(Caju roxo), Ziziphus joazeiro Mart (Juá), Erythrina velutina Willd (Mulungu) and Myracrodruon urundeuva (Engl.) Fr. All (Aroeira).The most used part of the plant was the bark, either fresh or dried, prepared as a decoction, and predominantly used as a mouthwash. Most plants are native and found in the community. These Quilombo communities are holders of traditional knowledge and practices in oral health, and are knowledgeable about plant species that can be used therapeutically in dentistry and that are found in the paraíban agreste‟s caatinga biome. The study documented the use of several medicinal plants that could be investigated pharmacologically. There are only a handful of ethnobotanical studies of medicinal plants aimed exclusively at the dental field, that have been carried out with these ethnic groups and in the caatinga biome.